2022
DOI: 10.3390/pr10020415
|View full text |Cite
|
Sign up to set email alerts
|

Genistein, a Potential Phytochemical against Breast Cancer Treatment-Insight into the Molecular Mechanisms

Abstract: Breast cancer (BC) is one of the most common malignancies in women. Although widespread successful synthetic drugs are available, natural compounds can also be considered as significant anticancer agents for treating BC. Some natural compounds have similar effects as synthetic drugs with fewer side effects on normal cells. Therefore, we aimed to unravel and analyze several molecular mechanisms of genistein (GNT) against BC. GNT is a type of dietary phytoestrogen included in the flavonoid group with a similar s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

7
3

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 161 publications
0
25
0
Order By: Relevance
“…Amentoflavone (biflavonoid) is one of the plant derivatives compounds that were isolated by Okigawa et al [ 16 ], and due to a wider range of bioactivities, it has drawn much attention among the scientific community [ 3 , 66 , 67 ]. A compound should have some fundamental properties for becoming an ideal anti-COVID-19 drug candidate [ 44 ] such as (i) restriction ability of viral entrance, thereby inhibiting cellular attachment; (ii) inhibition of viral replication inside the host cells; (iii) cytotoxic effects on the existing viruses; and (iv) protection of the host normal cells from the viral origin oxidative stress and inflammatory responses.…”
Section: Discussionmentioning
confidence: 99%
“…Amentoflavone (biflavonoid) is one of the plant derivatives compounds that were isolated by Okigawa et al [ 16 ], and due to a wider range of bioactivities, it has drawn much attention among the scientific community [ 3 , 66 , 67 ]. A compound should have some fundamental properties for becoming an ideal anti-COVID-19 drug candidate [ 44 ] such as (i) restriction ability of viral entrance, thereby inhibiting cellular attachment; (ii) inhibition of viral replication inside the host cells; (iii) cytotoxic effects on the existing viruses; and (iv) protection of the host normal cells from the viral origin oxidative stress and inflammatory responses.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Lui et al 2021, successfully demonstrated that genistein can specifically bind to DNA-dependent protein kinase catalytic subunit (DNA-PKcs) and block the DNA-PKcs/Akt2/Rac1 pathway, thereby effectively inhibiting radiation-induced invasion and migration of glioblastoma multiforme (GBM) cells in vitro and in vivo [ 296 ]. In addition, this phytochemical synergistically reverses the resistance mechanism of standard chemotherapeutic drugs, increasing their efficacy against BC [ 297 ].…”
Section: Plant-derived Natural Products With Potential Anticancer Eff...mentioning
confidence: 99%
“…Since the 1990s, most of the proposed autophagy pharmacological targets have been kinases, which are easily targetable with small molecules with substantial contribution and efficacy [ 115 ]. However, few compounds have translated into therapeutic use due to the uncertainty and debate concerning the effect of autophagy on cancer [ 116 ]. The ULK1 kinase complex, which includes the serine/threonine kinase ULK1 (ATG1), ATG7, and RB1 inducible coiled-coil 1 (RB1CC1, also known as FIP200), is activated in response to nutrient deficiency and is required for the induction of deprivation autophagy [ 117 ].…”
Section: Pharmacological Modulation Of Autophagy In Pdac Regulationmentioning
confidence: 99%